Perceptual Study of User Comfort Regarding The Temperature Comfort of Learning Teaching Space in Building B of The Faculty Engineering, Architecture Department, Lampung University. - Salsabila R, Syifa; Nugroho, Agung Cahyo (Journal of Engineering and Scientific Research, 2025)
This study addresses the importance of thermal comfort in educational spaces, focusing on Building B at the Faculty of Engineering, Lampung University, where tropical climate conditions and suboptimal thermal control systems often result in uncomfortable room temperatures. The study aims to assess architecture students' perceptions of thermal comfort in classrooms and analyze the impact of temperature on their learning comfort. A quantitative research method was employed, collecting data through direct observation and questionnaires distributed to students. Results indicate that classroom temperatures do not meet optimal comfort standards, with most students feeling discomfort due to excessive heat, which affects concentration and productivity. The study concludes by recommending improvements in cooling and ventilation systems within classrooms to create a more conducive learning environment for architecture students in tropical regions.